cho [tex]\left\{\begin{matrix} a^{3}-3ab^{2}=5 & & \\ b^3-3a^{2}b=10& & \end{matrix}\right.[/tex]
Tính [tex]a^{4}-a^{2}b^{2}-2b^{4}-4a^{2}+11b^{2}-5[/tex]
biết [tex]a^{2}+b^{2}=5[/tex]
Từ giả thiết ta có:
[tex](a^3-3ab^2)^2+(b^3-3a^2b)^2=5^2+10^2=125\\\Leftrightarrow a^6-6a^4b^2+9a^2b^4+b^6-6a^2b^4+9a^4b^2=125\\\Leftrightarrow a^6+b^6+3a^4b^2+3a^2b^2=125\\\Leftrightarrow (a^2+b^2)^3=125\\\Leftrightarrow a^2+b^2=\sqrt[3]{125}=5[/tex]
Xét [tex]a^{4}-a^{2}b^{2}-2b^{4}-4a^{2}+11b^{2}-5\\=(a^2+b^2)^2-3a^2b^2-3b^4-4a^2+11b^2-5\\=5^2-3b^2(a^2+b^2)-4a^2+11b^2-5\\=25-15b^2-4a^2+11b^2-5\\=20-4(a^2+b^2)\\=20-4.5\\=0[/tex]